2019
DOI: 10.1108/ils-10-2018-0104
|View full text |Cite
|
Sign up to set email alerts
|

Predictive analytic models of student success in higher education

Abstract: Purpose Many higher education institutions are investigating the possibility of developing predictive student success models that use different sources of data available to identify students that might be at risk of failing a course or program. The purpose of this paper is to review the methodological components related to the predictive models that have been developed or currently implemented in learning analytics applications in higher education. Design/methodology/approach Literature review was completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 56 publications
0
25
0
2
Order By: Relevance
“…Examining the methods for predictive analytics in higher education is another common theme in the literature. For example, most review papers in this area (e.g., Cui et al, 2019;Shahiri & Husain, 2015) have identified the most commonly used machine learning classifiers, such as logistic regression, decision tree, naïve Bayes, support vector machine, neural networks, and k-nearest neighbours. In addition, many studies on predictive analytics compared the prediction performance between different machine learning classifiers.…”
Section: Methods For Predictive Analyticsmentioning
confidence: 99%
See 3 more Smart Citations
“…Examining the methods for predictive analytics in higher education is another common theme in the literature. For example, most review papers in this area (e.g., Cui et al, 2019;Shahiri & Husain, 2015) have identified the most commonly used machine learning classifiers, such as logistic regression, decision tree, naïve Bayes, support vector machine, neural networks, and k-nearest neighbours. In addition, many studies on predictive analytics compared the prediction performance between different machine learning classifiers.…”
Section: Methods For Predictive Analyticsmentioning
confidence: 99%
“…Despite the success of these methods and their variants, using machine learning techniques for predictive modelling often requires many attempts at data preprocessing and feature engineering since structured datasets are often required for most machine learning classifiers. Not many studies have explicitly reported how they preprocessed data and extracted features (Cui et al, 2019), and there is no explicit guidance on how to do data pre-processing and feature engineering. This may be because different datasets require different pre-processing procedures, and the selection of features is often arbitrarily decided by how researchers think of the potential factors influencing learning outcomes.…”
Section: Methods For Predictive Analyticsmentioning
confidence: 99%
See 2 more Smart Citations
“…An adequate student model is a condition for making the right pedagogical decisions. In the review [4], the authors identify methodological strengths and weaknesses of current predictive learning analytics applications and provide the most up-to-date recommendations on predictive model development, use and evaluation. The study described in the article [5] provides an overview of the progress made to date in learning analytics, that uses techniques, methods, and algorithms that allow the user to discover and extract patterns in stored educational data, with the purpose of improving the teaching-learning process.…”
Section: Introductionmentioning
confidence: 99%